Rasio Neutrofil-Limfosit (NLR) sebagai Penanda Disfungsi Hati pada Pendonor Darah Sukarela di Unit Transfusi Darah Palang Merah Indonesia - Qurrotu A'yuni Auliya; Ririh Jatmi Wikandari; Bambang Supriyanta; Duwi Pudjiastuti; Yunita Rusidah (Jaringan Laboratorium Medis, 2026)
Background: HBsAg is a marker for hepatitis B virus, which causes liver dysfunction characterized by elevated serum glutamic pyruvic transaminase (SGPT) levels. The neutrophil-lymphocyte ratio (NLR) has a positive effect on SGPT. Objective: To describe NLR as a marker of liver dysfunction in voluntary blood donors at the PMI Blood Donation Unit (UDD). Methods: Descriptive study to determine the role of NLR as a marker of liver dysfunction in voluntary blood donors. The study population consisted of voluntary blood donors at the PMI Blood Donation Unit in Salatiga, Central Java. Primary data collected through complete blood tests and SGPT measurements. Secondary data were HBsAg results in voluntary donors. Results: All 20 respondents (100%) had an average SGPT level of 20 U/L and non-reactive HBsAg results, with an average NLR value of 1.76. The highest age group was 26-35 years old, with 8 respondents (40%). Based on gender, 15 respondents (75%) were male and 5 respondents (25%) were female. The percentage of blood types A and O was 8 respondents (40%), while blood types B and AB were represented by 2 respondents (10%). Conclusions: NLR cannot be used as a marker of liver dysfunction based on SGPT and HBsAG parameters.